2010
DOI: 10.1292/jvms.09-0494
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Nephrolithiasis in a Galician Blond Beef Calf

Abstract: ABSTRACT. A six-month-old female Galician Blond beef calf presented signs of apathy, anorexia and weight loss. The analysis of a blood sample confirmed renal failure. Bilateral nephrolithiasis was diagnosed at necropsy. Quantitative analysis revealed the nephroliths to be composed of 100 per cent xanthine. In cattle, xanthinuria has only been described in the Japanese Black breed, but never before in other breeds. Clinical history suggested a naturally occurring xanthinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…deformity or overgrowth of hooves have been previously reported in cases of renal dysplasia in cattle [6, 10]. In papers describing xanthinuria in cattle, it was not possible to find reports of overgrown hooves [14, 15], but such features could be an indicator of a general sign of renal failure (along with poor growth) and not of a specific disease. The very limited number of cases prevents us from observing in detail how the position and specific nature of the mutation affect the onset and severity of xanthinuria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…deformity or overgrowth of hooves have been previously reported in cases of renal dysplasia in cattle [6, 10]. In papers describing xanthinuria in cattle, it was not possible to find reports of overgrown hooves [14, 15], but such features could be an indicator of a general sign of renal failure (along with poor growth) and not of a specific disease. The very limited number of cases prevents us from observing in detail how the position and specific nature of the mutation affect the onset and severity of xanthinuria.…”
Section: Resultsmentioning
confidence: 99%
“…This autosomal recessive inherited disease has been associated with a 3 bp deletion in the coding region of the molybdenum cofactor sulfurase ( MOCOS ) gene . In a single genetically uncharacterized Galician Blond beef calf, signs of listlessness and weight loss and renal failure with bilateral nephrolithiasis, composed of 100% xanthine were reported [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a study on sheep with xanthine calculi concluded that low dietary molybdenum could be causative because of molybdenum's role in purine metabolism . Hereditary xanthinuria has been reported in cats (OMIA 001283‐9685), dogs (OMIA 001283‐9615), and cattle (OMIA 001819‐9913) . In some reports, the genetic basis was established by sequencing; in other cases, a primary cause was presumed after eliminating a history of XDH inhibitor use .…”
Section: Discussionmentioning
confidence: 99%
“…In higher animals other than primates, xanthinuria is lethal due to kidney damage resulting from xanthine stones in the urinary tract [2830], and this is explained by an acquired tolerance to oxypurines by primates that followed the loss of uricase during evolution [31]. …”
Section: Discussionmentioning
confidence: 99%